Light along curves: photonic shaping tools - Flamm, Daniel; Hellstern, Julian; Kaiser, Myriam; Kahmann, Max; Kleiner, Jonas; Tillkorn, Christoph (Advanced Optical Technologies, 2023)
A structured light concept is reported enabling to distribute a large number of focus copies at arbitrary positions in a working volume. Applying this holographic 3D-beam splitter concept to ultrashort laser pulses allows to deposit energy along accelerating trajectories in the volume of transparent materials. Based on the entirety of the volume modifications created in this way, the material can be separated, for example, to create chamfered glass edges. These photonic tools impress with enormous versatility, which enable equally diverse application strategies ranging from cutting and welding to data storing.